United States : Staff Report for the 2000 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Sound monetary and fiscal policies have contributed to making the current U.S. economic expansion the longest on record. Executive Directors welcomed these developments, and congratulated the U.S. authorities on the adoption of the Gramm-Leach-Bliley Act, which represents a much needed overhaul of the outdated laws regulating the financial sector in the country. They commended the improvements in market access provided by the enacted African Growth and Opportunity Act and the Caribbean Basin Initiative, and encouraged the U.S. government to complete the necessary financing arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet